2007
DOI: 10.1073/pnas.0704433104
|View full text |Cite
|
Sign up to set email alerts
|

RARα-PLZF overcomes PLZF-mediated repression of CRABPI , contributing to retinoid resistance in t(11;17) acute promyelocytic leukemia

Abstract: Leukemia-associated chimeric oncoproteins often act as transcriptional repressors, targeting promoters of master genes involved in hematopoiesis. We show that CRABPI (encoding cellular retinoic acid binding protein I) is a target of PLZF, which is fused to RAR␣ by the t(11;17)(q23;q21) translocation associated with retinoic acid (RA)-resistant acute promyelocytic leukemia (APL). PLZF represses the CRABPI locus through propagation of chromatin condensation from a remote intronic binding element culminating in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 62 publications
0
55
0
Order By: Relevance
“…The t(11;17) APL is mostly of poor prognosis, and the disease is relatively RA-resistant, possibly due to RA-resistant corepressor recruitment (33) and/or CRABPI derepression (16). Additionally, the inhibition of C/EBPe by PLZF-RARα (34) and the inhibition of C/EBPα by RARα-PLZF reported here, both required for terminal granulocytic differentiation, unequivocally contribute to this RA resistance and support the use of HDAC inhibitors for the treatment of t(11;17) APL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The t(11;17) APL is mostly of poor prognosis, and the disease is relatively RA-resistant, possibly due to RA-resistant corepressor recruitment (33) and/or CRABPI derepression (16). Additionally, the inhibition of C/EBPe by PLZF-RARα (34) and the inhibition of C/EBPα by RARα-PLZF reported here, both required for terminal granulocytic differentiation, unequivocally contribute to this RA resistance and support the use of HDAC inhibitors for the treatment of t(11;17) APL.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, RARα-PLZF binds to DNA via the PLZF binding site and derepresses PLZF target genes such as cyclin A, Hoxb2a and c-Myc (13)(14)(15), thereby causing increased proliferation. In addition, RA resistance has been associated with an up-regulation of cellular retinoic acid binding protein 1 (CRABPI) (16), although additional mechanisms could also contribute to this resistance. Furthermore, how RARα-PLZF modifies the tumor phenotype remains to be clarified.…”
mentioning
confidence: 99%
“…Several studies (19,20) on PLZF-RARA revealed that the PLZF moiety recruits corepressors and polycomb group proteins in an ATRA-insensitive manner and directly deregulates PLZF target genes to induce leukemia. In addition, reciprocal RARA-PLZF fusion protein also contributes to leukemogenesis (21,22). However, the molecular basis for induction of aberrant self-renewal capacity by PLZF-RARA is unclear.…”
mentioning
confidence: 99%
“…cited therein). The RARA, PLZF and BCR genes are known to be involved in translocations generating fusion proteins that play a critical role in leukemogenesis (6). A number of BAC clones mapped to five known common fragile sites (CFS) were also used.…”
Section: Introductionmentioning
confidence: 99%